Mission as Kinship on the Margins - Sedmak, Clemens (International bulletin of mission research, 2018)
Mission, according to Evangelii gaudium, is characterized by missionary joy, a kind of displacement, the experience of being evangelized by the poor, and the image of the bruised church. Such an understanding invites us to go to the margins and there encounter the Christ. This article develops the concept kinship on the margins in conversation with Greg Boyle's understanding of kinship. It distinguishes four types of kinship (based on blood, milk, water, or wine) and offers a case study of kinship on the marginsthe work of Georg Sporschill, SJ, in eastern Europe, which is an expression of a church of the poor.